Perbedaan kemampuan komunikasi matematik siswa diajar reciprocal teaching dengan pendekatan metakognitif dan diajar pendekatan ekspositori (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This research aims to determine whether there are differences in mathematical communication skills of students who are taught Reciprocal Teaching with metacognitive approaches and those who are taught expository approaches. This type of research is experiment research. The population in this study were all students of students of SMP Negeri 17 Medan. Sampling in this study were all class VII which was then chosen by two classes. The experimental class I (grades VII-8) were taught using Reciprocal Teaching with a metacognitive approach and the control class (grades VII-7) were taught with an expository approach. This research instrument was in the form of pre-test and post-test in the form of essay tests and consisted of 5 questions. Before the instrument is given to students, it is first validated to two mathematics lecturers and a mathematics teacher. Before testing the hypothesis, the normality and homogeneity of the data are tested. Based on the results of the analysis, the rate of change in mathematical communication skills is higher in the experimental class than in the control class .  Then it is concluded that there is a significant difference between students' mathematical communication skills taught by Reciprocal Teaching with metacognitive and expository approaches.
Keywords: mathematical communication skill; reciprocal teaching; metacognitive approaches